New insight into the analgesic recipe: A cohort study based on smart patient-controlled analgesia pumps records - Song, Yiyan; He, Qiulan; Huang, Wenzhong; Yang, Lu; Zhou, Shaopeng; Xiao, Xiaoyu; Wang, Zhongxing; Huang, Wenqi (Frontiers in Pharmacology, 2022)
Purpose: Intravenous patient-controlled analgesia (IV-PCA) has been widely used without an established criteria in regimen. In China, the most often used opioid was sufentanil which may rise concern of repeating dose, and flurbiprofen axetil (FBP) was commonly used as adjuvant empirically. We hypothesized that hydromorphone was a better choice and evaluated the effectiveness of FBP as adjuvant. Methods: We conducted a historical cohort study in two tertiary hospitals in China. 12,674 patient using hydromorphone or sufentanil for IV-PCA between April 1st 2017 and January 30th 2021 were included. The primary outcome was set as analgesic insufficiency at static (AIS). Secondary outcomes included analgesic insufficiency with movement (AIM), and common opioid related adverse effects such as postoperative nausea and vomiting (PONV) and dizziness. Results: We found Sufentanil, but not sufentanil-FBP combination, was associated with a higher risk of both AIS and AIM compared with hydromorphone (OR 1.64 [1.23, 2.19], P < 0.001 and OR 1.42 [1.16, 1.73], P < 0.001). Hydromorphone combined with FBP also decreased the risk of both AIS and AIM compared with pure hydromorphone (OR 0.74 [0.61, 0.90], P = 0.003 and OR 0.80 [0.71, 0.91], P < 0.001). However, a higher risk of PONV was noted in patient≤35 years old using FBP (hydromorphone-FBP vs hydromorphone and sufentanil-FBP vs hydromorphone, OR 1.69 [1.22, 2.33], P = 0.001 and 1.79 [1.12, 2.86], P = 0.015). Conclusion: Hydromorphone was superior to sufentanil for IV-PCA in postoperative analgesia. Adding FBP may improve the analgesic effect of both hydromorphone and sufentanil but associated with an increased risk of PONV in patient less than 35 years old.